Fabrication of a multimode interference device in a low-loss flat-fiber platform using physical micromachining technique - Ambran, S.; Holmes, C.; Gates, J.C.; Webb, A.S.; Carpenter, L.G.; Adikan, Faisal Rafiq Mahamd; Smith, P.G.R.; Sahu, J.K. (Institute of Electrical and Electronics Engineers, 2012)
A physical micromachining technique is demonstrated in a low-loss flat-fiber substrate to fabricate a multimode interference (MMI) device. The flat-fiber substrate is a low-index-contrast material; however, by making use of two physically micromachined trenches, lateral confinement is achieved providing high index contrast for the MMI region. A 1 x 3 MMI device exhibiting 1.89 dB of excess loss has been demonstrated.